Use of data from the Vascular Quality Initiative registry to support regulatory decisions yielded a high return on investment. Issue 1 (29th October 2020) - Cronenwett, Jack L; Avila-Tang, Erika; Beck, Adam W; Bertges, Daniel; Eldrup-Jorgensen, Jens; Resnic, Frederic S; Radoja, Nadezda; Sedrakyan, Art; Schick, Andreas; Smale, Josh; Bloss, Roberta A; Phillips, Peter; et al.
Abstract : Background: Real-world data (RWD) from the Society for Vascular Surgery Vascular Quality Initiative (VQI) registry has been used to support US Food and Drug Administration (FDA) regulatory decisions regarding vascular devices. The variables of cost and time needed for these registry-based studies have not been previously compared to traditional, independent, industry studies that would otherwise have been conducted to support regulatory decisions. Objectives: To determine the potential value (cost and time saving and return on investment) created by device evaluation studies using the VQI registry infrastructure. Methods: We compared studies that used data from the VQI registry with estimated costs of independent industry studies (counterfactual studies) using an established model using design specifications determined by FDA reviewers. Results: We analyzed the initial six studies evaluating vascular devices for regulatory decisions using data from the VQI registry that generated evidence for four device manufacturers. Return on investment for these studies was estimated to be 143% and cost saving as 59% based on an actual per patient (with 5-year follow-up) cost of US$11K using VQI data versus US$26K from the counterfactual when averaged across all studies. Significant enrollment time savings (45%–71%) were also realized compared with industry-based estimates. Conclusions: The use of RWD from the VQI registry in this study and the transcatheter valve treatment coordinated registry network in a prior study indicates that substantial value was added to device evaluation projects by the reuse of registry data, with additional potential savings if linked claims data can be used instead of costly long-term in-person follow-up.